Investigation of heavy metal contamination and associated health risks in groundwater sources of southwestern Punjab, India - Bangotra, Pargin; Jakhu, Rajan; Prasad, Mukesh; Aswal, R. S.; Ashish, Ansumali; Mushtaq, Zainab; Mehra, Rohit (Environmental monitoring and assessment, 2023)
Human body exposure to various toxic and non-toxic heavy metals in groundwater is a significant health concern, especially in developing countries. The present study was planned and carried out to appraise the potential health risks of eight heavy metals (Mn, Co, Cu, As, Se, Cd, Hg, and Pb) in different water sources of the Mansa and Muktsar districts of Punjab. The measurements of heavy metals were performed using the inductively coupled plasma mass spectrometry (ICPMS) technique. The health (carcinogenic and non-carcinogenic) risks and doses (ingestion and dermal) associated with exposure to heavy metals in water were estimated from the measured concentrations using USEPA guidelines. The average concentrations of heavy metals were observed in the order of Mn (13.93) > Cu (13.12) > Se (4.14) > As (3.28) > Hg (3.27) > Pb (1.29) > Co (0.20) > Cd (0.10) μg L −1 . The results show that the Hg, Pb, As, and Se concentrations are above the guideline values of the World Health Organization (WHO) in 10.34%, 3.45%, 6.90%, and 6.90% locations, respectively. The high values of these heavy metals may be due to geogenic anthropogenic activities. The hazard quotients (non-carcinogenic risk) for ingestion and dermal exposures were observed in the range of 0.32–3.79 and 8.05 × 10 −6 –1.34 × 10 −4 , respectively. On the other hand, the carcinogenic health risks due to ingestion and dermal exposure were observed to be 0.02–0.38 and 6.67 × 10 −8 –1.15 × 10 −6 , respectively. The results of this study will be helpful to the drinking water supplying agencies, water resource development authorities, etc.